2016
DOI: 10.1190/geo2014-0225.1
|View full text |Cite
|
Sign up to set email alerts
|

Love-wave waveform inversion in time domain for shallow shear-wave velocity

Abstract: High-frequency surface-wave techniques are widely used to estimate S-wave velocity of near-surface materials. Surface-wave methods based on inversions of dispersion curves are only suitable to laterally homogeneous or smoothly laterally varying heterogeneous earth models due to the layered-model assumption during calculation of dispersion curves. Waveform inversion directly fits the waveform of observed data, and it can be applied to any kinds of earth models. We have used the Love-wave waveform inversion in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…More recently, the existence of a beyond‐VTI anisotropy was reconfirmed (Wookey et al, ). Horizontally polarized shear waves and their superpositions propagating as Love waves had a significant impact on recent near‐surface inversions (Dokter et al, ; Pan et al, ). Typically, inversions focus on the velocity of SH waves along the horizontal axis; below we investigate which trade‐offs are irresolvable in inversions of this particular mode.…”
Section: Spectral Sensitivity Matrices and Numerical Analysis Of Tradmentioning
confidence: 99%
“…More recently, the existence of a beyond‐VTI anisotropy was reconfirmed (Wookey et al, ). Horizontally polarized shear waves and their superpositions propagating as Love waves had a significant impact on recent near‐surface inversions (Dokter et al, ; Pan et al, ). Typically, inversions focus on the velocity of SH waves along the horizontal axis; below we investigate which trade‐offs are irresolvable in inversions of this particular mode.…”
Section: Spectral Sensitivity Matrices and Numerical Analysis Of Tradmentioning
confidence: 99%
“…They concluded that the estimation of a priori quality factors is critical for inverting seismic waves in the near-surface zone . Pan et al proposed to invert the Lovewaves in the time domain to reconstruct the S-wave velocity model at the near surface (Pan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al . () estimated coarse 2D blocky S‐wave velocity models using a conjugate gradient‐based FWI for synthetic and Love‐wave field data applications. On the ultrasonic scale Bretaudeau et al .…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, the authors where able to successfully estimate the near-surface P-and S-wave velocity distribution for frequencies up to 20 Hz. Pan et al (2016) estimated coarse 2D blocky S-wave velocity models using a conjugate gradient-based FWI for synthetic and Love-wave field data applications. On the ultrasonic scale Bretaudeau et al (2013) reconstructed the Pand S-wave velocity model of a physical scale model by a FWI of surface and body wave data.…”
mentioning
confidence: 99%